CMOS DC-DC converter for sensor applications - Chua, Geng Li (2017)
The purpose of the work delineated in this dissertation is to design a DC-DC buck (step-down) converter. Its 5V (1A for a 5Ω load) output is obtained from a 10V DC source and is controlled by means of a varying pulse-width-modulation (PWM) control signal. The DC-DC buck converter is designed on the basis of a power CMOS 0.18μm technology, and is verified by means of computer simulations. The simulations are first performed without CMOS circuitry, with an ideal square pulse signal source, and ideal passive components – an inductor, a capacitor, and a resistor. The CMOS circuits required for the DC-DC converter are subsequently added on step-by-step to model the contribution(s) of each introduced component, particularly to ascertain how the output deviates from the ideal output signal. The said CMOS circuits added step-by-step include the basic PMOS and NMOS transistors, level-up shifter, and the progressively sized-up inverters. The final output from the DC-DC with full circuitry is simulated and compared to the ideal DC-DC converter without CMOS circuitry.